Conservation of plasmid-encoded dibenzothiophene desulfurization genes in several rhodococci. - Denis-Larose, C (1997)
The cloned sulfur oxidation (desulfurization) genes (sox) for dibenzothiophene (DBT) from the prototype Rhodococcus sp. strain IGTS8 were used in Southern hybridization and PCR experiments to establish the DNA relatedness in six new rhodococcal isolates which are capable of utilizing DBT as a sole sulfur source for growth. The ability of these strains to desulfurize appears to be an exclusive property of a 4-kb gene locus on a large plasmid of ca. 150 kb in IGTS8 and ca. 100 kb in the other strains. Besides a difference in plasmid profile, IGTS8 is distinguishable from the other strains in at least the copy number of the insertion sequence IS1166, which is associated with the sox genes.